2006
DOI: 10.1038/sj.bjc.6603372
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Calman–Hine report on the processes and outcomes of care for Yorkshire's colorectal cancer patients

Abstract: The 1995 Calman -Hine plan outlined radical reform of the UK's cancer services with the aim of improving outcomes and reducing inequalities in NHS cancer care. Its main recommendation was to concentrate care into the hands of site-specialist, multi-disciplinary teams. This study aimed to determine if the implementation of Calman -Hine cancer teams was associated with improved processes and outcomes of care for colorectal cancer patients. The design included longitudinal survey of 13 colorectal cancer teams in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 17 publications
(12 reference statements)
2
59
0
Order By: Relevance
“…These aspects are par ticularly relevant considering the high-incidence of PC. However, there is lack of evidence indicating that MDT approach resulted in improvements in clinical outcomes because studies are retrospective, with poor sample size (12)(13)(14)16).…”
Section: Discussionmentioning
confidence: 99%
“…These aspects are par ticularly relevant considering the high-incidence of PC. However, there is lack of evidence indicating that MDT approach resulted in improvements in clinical outcomes because studies are retrospective, with poor sample size (12)(13)(14)16).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the MDTM is the forum in which all cancer patients are discussed and subsequent treatment decisions made and reviewed [4]. Studies have shown improved survival outcomes associated with cancer care delivered through a MDTM [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…6 In the colon and rectal cancer setting, one study found that the established management plan for patients with complex cases of colon or rectal cancer changed after multidisciplinary team discussions. 27 More generally, studies in the oncology setting have identified organizational-level characteristics of MDC [28][29][30] and investigated health and process outcomes of care associated with MDC and performance improvements in multidisciplinary teams. 17,[31][32][33] Although the evidence has been mixed regarding the effectiveness of MDC, it is difficult to make comparisons across studies because of the lack of a standard definition of MDC, variation in the measurement of MDC performance, and differences in the outcomes assessed.…”
Section: Colon Cancermentioning
confidence: 99%